Eksistensi Sanggah Kemulan Nganten dalam Upacara Perkawinan Masyarakat Desa Pedawa - Purniati, Ketut; Suarsana, I Nyoman; Sudiarna, I Gusti Putu (Humanis; Vol 24 No 3 (2020), 2020)
The community in Pedawa village, sub-district Banjar, districts Buleleng knows the term marriage they call with 'melaib' which is a local term which means to marry. Every man in Pedawa village who is married is obliged to make Sanggah Kemulan Nganten which is manifested in a series of wedding ceremonies. Sanggah Kemulan Nganten or also called sanggah tiing (a place of worship it made from bamboo) is a pelinggih (place of worship) symbol of the part of a new household from the individual. This study refers to understand and identify the process of the realization of Sanggah Kemulan Nganten in the marriage ceremony in the Pedawa village and, to find out and identify the meaning of Sanggah Kemulan Nganten in the life of the Pedawa village. The results of the study show that Sanggah Kemulan Nganten must be made by men. This refers to harmonize the household and block from the disease. Mandatory ceremony to establish  Sanggah Kemulan Nganten is ngamputang lis. The meaning of religion from Sanggah Kemulan Nganten is to establish the belief in the existence of supernatural powers from Sanggah Kemulan Nganten. The meaning of solidarity from Sanggah Kemulan Nganten is participation and community support in the activities of establishing Sanggah Kemulan Nganten. The cultural meaning of Sanggah Kemulan Nganten is namely the pedawa village community,believes in local traditions or culture, which is in accordance with the mandate that has been passed down by generations of pedawa village ancestors.